2021
DOI: 10.1016/j.jsps.2021.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy practice in hospital settings in GCC countries: Prescribing and transcribing

Abstract: Purpose To outline hospital pharmacy practices across the Gulf Cooperation Councils (GCC) countries’ hospitals. Methods A modified survey questionnaire was prepared from the original 2019 American Society of Health-System Pharmacist (ASHP) survey questions. Survey details were discussed with some pharmacy directors for clarity and relevance. A list of hospitals were obtained from the Ministry of Health of each of the targeted GCC countries. A secure invitation link cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Significant efforts were made to evaluate the current practice status for all the defined and expected pharmaceutical services. Several tools were used including national surveys, collecting information on current pharmacy workforce, and collaborating with regional 2 as well as seeking international evaluation from the American‐Society of Health System Pharmacists. The outcome from all the needs assessment highlighted the necessity to amend the pharmacy scope of practice to move from tradition roles to more patient centred professional activities.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Significant efforts were made to evaluate the current practice status for all the defined and expected pharmaceutical services. Several tools were used including national surveys, collecting information on current pharmacy workforce, and collaborating with regional 2 as well as seeking international evaluation from the American‐Society of Health System Pharmacists. The outcome from all the needs assessment highlighted the necessity to amend the pharmacy scope of practice to move from tradition roles to more patient centred professional activities.…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare systems have identified the inevitable role of the pharmacists in the multidisciplinary team with the introduction of new regulations and policies that have supported pharmacists and pharmaceutical services to be part of integrated healthcare services. 1,2 However, data from the Middle east countries showed that pharmacists' role is still limited, despite many recommendations to develop improvement strategies. [3][4][5][6][7] Pharmacy practice in Kuwait has long been identified as a sector yet to be developed, 4,8,9 with recommendations mainly urging to invest in undergraduate education and continuing professional development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation